Influence of Digital Trust and Transparency on Customer Loyalty in Online Banking Services during Rapid Technological Change - Mujito Mujito; Syamsurizal; Noorsidi Aizuddin Bin Hj. Mat Noor (Management Dynamics: International Journal of Management and Digital Sciences, 2024)
This study explores the significant role of digital trust and transparency in fostering customer loyalty in online banking services. As the financial sector increasingly shifts towards digital platforms, understanding the dynamics of customer retention becomes crucial for banking institutions. The research adopts a quantitative approach, using a survey questionnaire distributed to over 200 participants with experience in digital banking services. The findings reveal that both digital trust and transparency are pivotal in shaping customer loyalty. Specifically, digital transparency-in areas such as data security, privacy, and operational clarity-was found to have a stronger correlation with customer retention than trust alone. The study emphasizes that transparency not only boosts customer confidence but also strengthens long-term loyalty by reducing perceived risks and uncertainties. Additionally, the research highlights that customer engagement, driven by transparent communication and reliable services, plays a significant role in mediating the relationship between transparency and loyalty. The study further discusses the implications for banking institutions, suggesting that focusing on transparent practices, clear communication about security measures, and data usage can lead to enhanced customer satisfaction and long-term retention. Future research could investigate the impact of cultural differences on digital trust and transparency in banking, as well as explore the role of emerging technologies like blockchain in furthering transparency and trust in financial transactions.